Pengaruh Promosi dan Harga terhadap Loyalitas Konsumen dengan Kepuasan Konsumen sebagai Variabel Intervening (Studi Pada Konsumen Sepeda Motor Honda di Temanggung) - Surahman, Surahman; Indriyatni, Lies; Wahyuningsih, Susanti (STIE PENA, 2022)
The purpose of this study was to determine the effect of promotion and price on consumer satisfaction as an intervening variable, and the effect of promotion, price, and customer satisfaction on consumer loyalty. The research method used in this research is path analysis. The research population is Honda motorcycle consumers. The sample of this study was 120 people with a non-probability sampling technique with a purposive sampling approach, namely the researcher chose a purposive sample subjectively. The method of collecting data is by using a questionnaire distributed through the gppgle form. The type of data used is primary data. The results of this study indicate that promotion has an effect on consumer satisfaction and price has an effect on consumer satisfaction. Promotions and prices affect consumer loyalty, consumer satisfaction affects consumer loyalty. Promotion and price affect consumer loyalty with consumer satisfaction as an intervening variable.Keywords: Promotion, price, consumer satisfaction, and consumer loyalty